Pengaruh Harga, Lokasi dan Kualitas Layanan Perawatan Gigi Terhadap Kepuasan Pasien Klinik Gigi Drg. Rini Yulia, Sp.KG - Caroline, Pascalia Dwi (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the influence of price, location, and service quality on patient satisfaction at the Dental Clinic of Drg. Rini Yulia, Sp.KG. The research is based on the importance of understanding the factors that affect patient satisfaction, considering that patient satisfaction is one of the main indicators of the success of healthcare service delivery, particularly in dental care facilities. The increasingly intense competition in healthcare services requires every clinic to provide optimal care and meet patient expectations in order to maintain their loyalty. The proposed hypothesis states that price, location, and service quality have a positive and significant effect on patient satisfaction, both simultaneously and partially. This research employs a quantitative method with an associative approach. Primary data were collected through direct observation and the distribution of questionnaires to patients who were receiving or had received services at the clinic. The research instrument was designed to measure respondents’ perceptions of the three independent variables: price, location, and service quality. Data analysis was carried out using multiple linear regression to test the relationships and the extent of influence between these variables on patient satisfaction as the dependent variable. The results indicate that, simultaneously, the three independent variables price, location, and service quality have a significant effect on patient satisfaction. Partially, service quality contributes the most dominant influence compared to price and location. These findings indicate that service quality is a key factor that should become the top priority in dental clinic management, supported by reasonable pricing and the selection of a strategic location to ensure patient comfort and accessibility. The implication of this study is the need for continuous improvement in service aspects to maintain and enhance patient satisfaction, which ultimately can increase patient loyalty and strengthen the clinic’s positive reputation in the community.